A Simple Method for the Preparation of Stainless and Highly Pure Trichloroacetimidates - Ikeuchi, Kazutada; Murasawa, Kentaro; Yamada, Hidetoshi (Synlett, 2019)
We describe a method for obtaining various allylic, benzylic, and glucosyl 2,2,2-trichloroacetimidates (TCAIs) as stainless liquids or solids at the crude stage. The general synthetic method for the preparation of TCAIs often leads to stained products, and further purification of crude TCAIs causes decomposition due to their instability. In the described method, we use a solvent that barely dissolves the reactant, providing stainless and sufficiently pure TCAIs without requiring a purification step. Furthermore, the reaction mixture is turbid at the beginning and clear at the end, allowing us to monitor the progress of the reaction visually.
Keywords: preparation; 2,2,2-trichloroacetimidates; stainless; solvent optimization; visual detection